Recent progress in photocathodes for hydrogen evolution - Huang, Qiang; Ye, Zi; Xiao, Xudong (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
Solar water splitting, which has been a topic of intensive research interest for several decades, is one of the promising approaches to utilize renewable energy to maintain the sustainable prosperity of our society. However, until now no mature photoelectrochemical cell has been used in practical large-scale applications because of the difficulties to satisfy all the harsh requirements, including high energy conversion efficiency, high stability and low cost. This feature article reviews the recent progress in developing photocathodes for photoelectrochemical cells for solar hydrogen production. Both the development of the p-type semiconductor light absorbers and the efforts to develop synergistic approaches to improve the overall performance of the photocathode are discussed. Recent efforts to improve the performance of photocathodes for hydrogen evolution are reviewed.